The Effect of Capital Turnover on Business Profitability in MSMEs in Makassar City - Hasyim, Sitti Hajerah; Nurjannah (International Journal of Asian Business and Management, 2023)
Business people attach great importance to the company's working capital. The current use of working capital can be used to determine whether working capital management is effective or not. To find out how working capital influences profitability in MSMEs in Makassar City, working capital turnover which includes net sales, current assets and current liabilities is used as the main measurement method. In this research, every MSME in Makassar City is the population. Sample selection was carried out using a purposive selection method consisting of 10 MSME financial reports in the form of balance sheets and profit and loss statements for a five year period (2018–2022). According to research findings, profitability is positively influenced by working capital turnover